Pengaruh Sistem Pembayaran Non Tunai terhadap PDB Indonesia Tahun 2011-2021 - Gita Azura Larasati; Nugroho Sumarjiyanto Benedictus Maria (Universitas Diponegoro, 2023)
The development of technologies that demand faster and easier operation also encourages the development of payment systems, which is one of the components that can support economic growth. Innovation in the non-cash payment system developed by Bank Indonesia can help people to be able to do transactions easier and faster to fulfill their needs. This study aims to find out the effect of the non-cash payment system using electronic money (e-money) and Card-Using Payment Instruments (APMK) with debit/ATM cards and credit cards on Indonesia's Gross Domestic Product (GDP). The methods used in this study are multiple linear regression analysis with Ordinary Least Square (OLS) models. The type of data used is secondary data in the form of time series in quarterly intervals of the period 2011 to 2021 obtained from the website of Bank Indonesia and Badan Pusat Statistik. The results of the study showed that debit/ATM cards have a significant positive effect on GDP. Meanwhile, credit cards and electronic money do not have a significant effect on GDP. Simultaneously, debit/ATM cards, credit cards, and electronic money have a significant positive effect on GDP, which means that if the use of payments with Card-Using Payment Instruments (APMK) and electronic money (e-money) increases simultaneously, it will encourage an increase in Indonesia's GDP.